2022
DOI: 10.1155/2022/1725053
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Development of Niacinamide/Ferulic Acid‐Loaded Multiple Emulsion and Its In Vitro/In Vivo Investigation as a Cosmeceutical Product

Abstract: Objective. Multiple emulsions have the ability to incorporate both lipophilic and hydrophilic actives in the same preparation and facilitate permeation of active ingredients through skin. The current study was aimed at formulating niacinamide/ferulic acid-loaded stable multiple emulsion (MNF) and its in vitro/in vivo characterization as a cosmeceutical product. Methods. Both the compounds were evaluated for their radical scavenging potential by the DPPH method and FTIR analysis. Then, placebo and active formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…In vitro testing indicated that developed emulgel has great capacity for sun protection. Previous studies have demonstrated the ability of AGEA to protect skin against photodamage 40,41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro testing indicated that developed emulgel has great capacity for sun protection. Previous studies have demonstrated the ability of AGEA to protect skin against photodamage 40,41 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the ability of AGEA to protect skin against photodamage. 40,41 The rate-limiting steps in the production of melanin are mediated by the tyrosinase enzyme. When incubated with L-DOPA, relative tyrosinase activity can be measured.…”
Section: Skin Fine and Large Pore Analysismentioning
confidence: 99%
“…1,2 As several metabolic sequences obstruct the use of antioxidants and polyphenols in diet, 3 cosmetic products via topical and transdermal route are a paramount choice for the provision of these antioxidants for various skin ailments. 1 The use of transdermal drug delivery system with nanotechnology such as ethosomes is gaining much attention now a day, owing to their first-pass effect; safe and effectual transport of drugs. Ethosomes, being the lipid-based vesicular nano-carriers can encapsulate both hydrophilic and hydrophobic drugs, easily permeate through the skin because of the presence of higher amount of ethanol, are stable and non-irritant to the skin, can produce both local and systemic effects and release the drug over an extended period of time by acting as a depot.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants, by subsiding the excessive production of reactive oxygen species plus upgrading of antioxidant resistance of the body endogenously, lead toward enhanced elasticity and hydration along with reduced melanin level by shielding the skin from UVR damage. 1,2 As several metabolic sequences obstruct the use of antioxidants and polyphenols in diet, 3 cosmetic products via topical and transdermal route are a paramount choice for the provision of these antioxidants for various skin ailments. 1 The use of transdermal drug delivery system with nanotechnology such as ethosomes is gaining much attention now a day, owing to their first-pass effect; safe and effectual transport of drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation